Mutations Altering Chloroplast Ribosome Phenotype in Chlamydomonas, I. Non-Mendelian Mutations - Gillham, Nicholas W. (1970)
Uniparentally inherited mutations to antibiotic resistance and dependence in Chlamydomonas reinhardi exhibit an altered chloroplast ribosome phenotype. Genetic studies demonstrate an absolute correlation between the drug resistance or dependence and the ribosome phenotype in two such mutants.